DO CHILI FARMERS SATISFY WITH THE GISIK PRANAJI AUCTION MARKET SERVICE? - Nugroho, Agus Dwi; Wahyuni, Lutfiana; Hardyastutia, Suhatmini (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2021)
Indonesian farmers face numerous issues when marketing their products. To overcome this, it is necessary to strengthen agricultural institutions, especially the auction market. However, many auction markets have underperformed, leaving farmers dissatisfied. This study aimed to know the farmers’ satisfaction with the Gisik Pranaji services, the oldest auction market in the sandy coastal area of Indonesia. This study was conducted in Kulon Progo Regency (Indonesia) from February to March 2020. The respondents were 60 (sixty) farmers who were chosen by purposing sampling. The analysis models used in this study are the Likert scale and customer satisfaction index. Farmers' expectations regarding the tangibles, reliability, responsiveness, and empathy attributes are still unmet. Meanwhile, the auction market will only satisfy the farmers' expectations in the assurance attribute. In general, farmers being dissatisfied with the auction market services. This issue arises due to auction market services that do not follow the Standard Operating Procedure, human error, and insufficient facilities.